A bibliometric review of zero waste in the built environment using VOSviewer: evolution, hotspots, and prospects - Linglin, Zhou (Frontiers in Environmental Science, 2024)
The global construction industry presents a significant challenge to environmental sustainability, sparking increasing concerns regarding its environmental impact. Zero Waste (ZW) has become a comprehensive waste management approach within the construction sector. However, there is a notable absence of systematic reviews in this field. Bibliometrics has played a pivotal role in advancing new methodologies for systematic reviews. To address this gap, our study employs VOSviewer to systemati-cally review the research domain of ZW, exploring research trends, international collaborations, primary authors, research do-mains, and literature. Our findings reveal a pronounced upward trend in research dedicated to achieving zero waste goals in the built environment, aligning with escalating global environmental concerns. Research in this realm has thrived notably in China, Australia, and England, with these countries contributing significantly to relevant studies. Co-occurrence analysis highlights key themes, such as construction waste reduction, sustainable construction, circular design, prefabrication, and Building Information Modelling (BIM). Notably, system dynamics and BIM have emerged as crucial modelling techniques. Moreover, this study em-phasises the adoption of circular economy principles, the efficacy of prefabrication, and the role of BIM in waste management. Future research directions encompass exploring global variations, investigating the impact of technology, engaging stakehold-ers, and considering regulatory frameworks. Despite its limitations, this study underscores the mounting global interest in ZW research, providing a foundation for future exploration and collaboration in sustainable construction and environmental man-agement.